FINDINGS ON FRAUD IN FINANCIAL MANAGEMENT: PROFESSIONAL EXPERIENCE, EXPERTISE, AND PROFESSIONAL ETHICS OF GOVERNMENT INTERNAL SUPERVISORS - Irfansyah Putra; Nuraini A; Riha Dedi Priantana (Ravine Publisher, 2023)
The purpose of this study was to determine the effect of Professional Experience, Expertise, and Professional Ethics on Findings of SKPD Financial Management Fraud. The population in this study were all Government Internal Supervisors, totaling 28 people. The sample in this study is a census of 45 SKPD. Respondents in this study were 28 Auditors for Government Internal Supervisory Apparatuses. Data analysis in this study used multiple linear regression, which was processed with the SPSS program (Statistical Package For Social Science). The results showed that professional experience, expertise, and professional ethics (both jointly and simultaneously) positively and significantly affected findings of SKPD financial management fraud. Professional experience has a positive effect on findings of SKPD financial management fraud, the expertise of the government's internal supervisory apparatus partially has no effect on findings of SKPD financial management fraud, and professional ethics has a positive effect on findings of SKPD financial management fraud.